Perancangan Aplikasi Buku Tamu Berbasis Desktop Di SMK Setia Bhakti Menggunakan Metode Agile - Zain Darmawan , Fikri; Adam Fanrian, Aldi; Setiaji , Harits; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
With the advancement of information technology, applications have become a crucial need in various aspects of life, including education. SMK Setia Bhakti, as an innovative educational institution, needs to enhance its data management, particularly in guest book management. Manual guest book management often poses challenges in recording and securing data. Therefore, this research proposes the development of a digital guest book application to improve efficiency and information security. The research employs an agile methodology in system development, from planning to project closure. The application is expected to record guest data, manage information digitally, and generate reports more efficiently and securely. The system also utilizes XAMPP and Netbeans for data management and implementation. The results of this study indicate that the digital guest book application can meet the expected functional and non-functional requirements, providing a more effective solution compared to the manual method.